PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA GURU MENGGUNAKAN METODE PROFILE MATCHING STUDI KASUS DI MTS NEGERI BRANGSONG - Iwan Koerniawan; M. Mustofa (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
MTs Negeri Brangsong assesses teacher performance in learning in support of creation effective educational process in building disciplined attitudes and student learning outcomes. Good teacher performance wil produce good student learning achievement. The purpose of this study was to design a decision support system for teacher performance appraisal in MTs Brangsong Country. The method used by the author is the profile matching method, because the method is very suitable for use in decision support systems for teacher performance evaluation with profile standards. Software that is used are Microsoft Visual Basic 6.0, MySQL database and Crystal Report as report generation software. The results of the teacher performance appraisal decision support system are data input, data search, value processing and reporting will be easier and data security more secure.